Dawność jako jeden z wyznaczników wartości pojęć etycznych i społecznych w czasach średniopolskich = Antiquity as one of the determinants of the values of ethical and social concepts in the Middle Polish period - Raszewska-Żurek, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is devoted to one of the means of expressing positive evaluation of the concepts in the early Polish language. It has to do with the assigning of the property of antiquity to the names of the moral and social values. This process takes place in three ways.
Keywords: historia polszczyzny; aksjolingwistyka; wartościowanie w języku; history of the Polish language; axiolinguistics; evaluation in language